A study of the drug tildrakizumab for plaque psoriasis. (1st June 2020) - Kimball, A.B.; Papp, K.A.; Reich, K.; Gooderham, M.; Li, Q.; Cichanowitz, N.; La Rosa, C.; Blauvelt, A.
Summary: Tildrakizumab is a fairly new type of medicine called a biologic, used for the treatment of moderate‐to‐severe psoriasis. The drug prevents the action of a specific molecule in the body involved in inflammation, known as cytokine interleukin (IL)‐23p19. Previous studies have shown it to be superior to a placebo (an inactive substance, like a "sugar pill") and to an older biologic drug, the TNF inhibitor etanercept. However, trials rarely reflect real‐world experience, where patients may switch from one drug to another, change drug dosage or interrupt treatment, e.g. because of an infection. The authors, based in U.S.A., Canada and Germany, reviewed results from two studies, one comparing two different doses of tildrakizumab (100mg or 200mg per day) with placebo, and the other comparing it with etanercept, including a total of 1862 adults with moderate‐to‐severe plaque psoriasis. Treatments were re‐randomised during the course of the study. They found that the response to tildrakizumab was sustained (meaning it kept working), without the secondary failure (decreasing responsiveness to a drug after an initial satisfactory response) seen in some patients on etanercept, and the drug regained effective control of the psoriasis after treatment was interrupted. Overall the drug was well tolerated, meaning that side effects were minimal. This is a summary of the study: Efficacy and safety of tildrakizumab for plaque psoriasis with continuous dosing, treatment interruption, dose adjustments and switching from etanercept: results from phase III studies